Analisis problematika guru dalam pelaksanaan pembelajaran daring pada siswa kelas rendah sekolah dasar - Anidaa Elsa Iftinaan; Siti Istiyati; Siti Kamsiyati (Universitas Sebelas Maret, 2022)
The purpose of this study to describe the implementation of online learning, learning problems experienced by teachers, and the solutions used to overcome the problems that arise in the implementation of online learning in SD Negeri 1 Krasak Boyolali. This research is a descriptive qualitative research. The subjects in this study were second grade teachers at SD Negeri 1 Krasak Boyolali. Data collection techniques through observation, interviews, and documentation. The validity test of the data used in this research is triangulation of sources and triangulation techniques. The data analysis techniques used in this study using Miles and Huberman analysis model consisting of data collection, data reduction, data display, and conclusion drawing/verification. The result showed that there were problems experience by grade II teachers when conducting online learning activities. At the planning stage teachers experience problems when preparing online lesson plans, at the implementation stage teachers experience problems when supervising and delivering learning materials, while at the evaluation stage teachers experience problems in assessing knowledge, attitudes, and skills. The conclusion of this study is that the problems experienced by teachers during online learning activities can be found a solution by adjusting the state of students and the school environment.